2020
DOI: 10.1021/acs.joc.9b02953
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Furo[3,2-b]quinolines and Furo[2,3-b:4,5-b′]diquinolines through [4 + 2] Cycloaddition of Aza-o-Quinone Methides and Furans

Abstract: An approach for the construction of furo­[3,2-b]­quinolines and furo­[2,3-b:4,5-b′]­diquinolines is developed through a metal-free [4 + 2] cycloaddition of easily available in situ generated aza-o-quinone methides and furans. The reaction tolerates a wide range of aza-o-quinone methides and substituted furans to afford the corresponding dihydro- or tetrahydrofuroquinolines in good to excellent yields. Mechanistic studies reveal that the reaction involves a concerted [4 + 2] cycloaddition pathway and shows a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…14 The Mo research group designed a synthesis of furo [3,2-b]quinolines and furo[2,3-b:4,5-b′]diquinolines through a metal-free [4+2] cycloaddition of furans and easily available aza-ortho-quinone methides, generated in situ (Scheme 2b). 15 The Shao research group reported a method for the synthesis of 1,2,3,5-tetrahydro-4,1,3-benzoxadiazepines in excellent yields through [4+3] cycloaddition of [o-(chloromethyl)aryl]sulfonamides with nitrones (Scheme 2c). 16 To construct functionalized 1,2,4-…”
Section: Letter Synlettmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The Mo research group designed a synthesis of furo [3,2-b]quinolines and furo[2,3-b:4,5-b′]diquinolines through a metal-free [4+2] cycloaddition of furans and easily available aza-ortho-quinone methides, generated in situ (Scheme 2b). 15 The Shao research group reported a method for the synthesis of 1,2,3,5-tetrahydro-4,1,3-benzoxadiazepines in excellent yields through [4+3] cycloaddition of [o-(chloromethyl)aryl]sulfonamides with nitrones (Scheme 2c). 16 To construct functionalized 1,2,4-…”
Section: Letter Synlettmentioning
confidence: 99%
“…Because the influence of the base was crucial for the reaction, various bases were then screened. The yield was not improved by using other bases such as Na 2 CO 3 , Cs 2 CO 3 , NaHCO 3 , KOH, or DIPEA instead of K 2 CO 3 (entries [10][11][12][13][14][15][16]; in the presence of Et 3 N or DBU, the reaction failed to work and no product was obtained (entries 15 and 16). Endeavors to improve the efficiency of the reaction by varying the ratio of 1a and 2a proved to be in vain (entries 17 and 18).…”
Section: Letter Synlettmentioning
confidence: 99%
“…Besides indoles, dearomatization of furans is also one of the useful protocols to access complex target molecules. 16 In 2020, Mo, Lu and co-workers 17 Another contribution concerning the alkene moiety as a twoatom reaction partner was described by the Wang group. 18 They accomplished an efficient [4+2] cycloaddition of [60]fullerene 48 with o-chloromethyl aniline compounds 47 in the presence of Cu2O and 1,10-phenanthroline, affording a series of fullerotetrahydroquinolines 49.…”
Section: Scheme 7 Total Synthesis Of (+)-Perophoramidine Through An Asymmetric Biomimetic [4+2] Cycloaddition Between the Substituted Trymentioning
confidence: 99%
“…Besides indoles, dearomatization of furans is also a useful protocol to access complex target molecules. 16 In 2020, Mo, Lu and co-workers 17 Another contribution concerning the alkene moiety as a two-atom reaction partner was described by the Wang group. 18 Readily available carboxylic acids were found to be efficient precursors to NHC (N-heterocyclic carbene) enolates through an in situ activation strategy.…”
Section: Scheme 7 Total Synthesis Of (+)-Perophoramidine Through An Asymmetric Biomimetic [4+2] Cycloaddition Between a Substituted Tryptmentioning
confidence: 99%
“…[4 + m] Annulation of in situ formed aza-o-QMs has been extensively studied to construct various nitrogen-containing heterocycles in the past decades. [11] On the other hand, pyridinium 1,4-zwitterionic thiolates, which could be conveniently synthesized from a multi-component reaction of sulfur, dialkyl acetylenedicarboxylates and pyridine, were a type of particularly powerful sulfur-containing synthon. [12] They have been successfully applied to synthesize various sulfur-containing heterocycles, such as thiophenes, pyridothiazepines and 1,4benzothiophenes.…”
mentioning
confidence: 99%